ANALYSIS OF THE INFLUENCE OF IMPLEMENTING INTERPROFESSIONAL COLLABORATION PRACTICE ON THE QUALITY OF INTEGRATED ANTENATAL CARE SERVICES AT PEBAYURAN BEKASI HEALTH CENTER IN 2023 - Yulastri, Siti Aisyah; Khairiah, Rahayu (HEARTY, 2025)
Background: In facing the complex health problems of patients today, health professionals are required to provide excellent and quality health services. Handling health problems requires a comprehensive and collaborative approach between professionals. Research Objective: To determine the effect of implementing Interprofessional Collaboration Practice on the quality of integrated antenatal care services at the Bekasi Pebayuran Community Health Center in 2023. Research Method: The research design used in this research is cross-sectional. with the population in this study being Health Workers at the Bekasi Pebayuran Community Health Center, totaling 40 people." The sample was determined using a total sampling of 40 people. Research Results: The correlation value shows 0.513 with a sample of 40, which means the variable relationship is strong and positive. In accordance with the conclusion of the t test with the condition p<0.05, Ha is accepted and the result is a significance level of 0.0001, which means significance is at the 0.0001 level, lower than 0.05. Conclusions and Suggestions: There is an influence of the implementation of Interprofessional Collaboration Practice on the Quality of Integrated Antenatal Care Services at the Pebayuran Bekasi Health Center in 2023. For the health center, it can be used as information and evaluation of health services at the health center, especially ANC services and for the head of the health center it is recommended to hold seminars or activities regular workshops related to IPC / interprofessional collaboration.